Daya Tarik Wisata Musik dalam Meningkatkan Kunjungan Wisatawan ke Kota Bandung - Alim, Azmi Kautsar; Noor, Any Ariani (Tourism Scientific Journal, 2024)
Today, music tourism is multiplying due to a shift in tourism trends from mass tourism to more personalized tourism activities or special interest tourism. This shift in tourism trends has a positive impact on the city of Bandung, which is famous for the creativity of its young people and produces many famous musicians and music festivals in Indonesia. This study aims to identify the influence of music tourism attraction on the motivation of tourists visiting Bandung. Mixed methods through in-depth interviews with music tourism providers and distributing questionnaires to 100 respondents who have attended music performances in the city of Bandung were used to collect comprehensive and in-depth data. The results show that the city of Bandung has fulfilled the four components of tourism. Meanwhile, the results of the quantitative analysis show that music tourism has the potential to influence the motivation of tourists visiting Bandung City.